Feeding of culled carrot to growing rabbits: effect on growth, nutrient utilization and blood biochemical profile: Growth, nutrient utilization, cholesterol level and antioxidant status - Saha, S. K.; Rathod, Akash (International Journal of Livestock Research, 2024)
The effect of feeding culled carrots on growth, nutrients utilization and blood biochemical profile of rabbits were analysed. In the 90 d of the feeding trial, 21 New Zealand White rabbits (Oryctolagus cuniculus) were divided into three groups of 7 rabbits each. Rabbits in group I were only fed with a concentrate mixture, whereas, those in groups II and III were fed with a concentrate mixture mixed with culled carrots @ 10% and 20% (on DM basis) respectively. Green berseem was offered ad lib to fulfil the remaining nutritional requirements. The proximate composition, total phenolic contents and DPPH assay of the culled carrot were estimated before feeding. The body weight gain and nutrients digestibility were estimated at the middle of feeding trail. Blood biochemical profile and antioxidant activity in rabbit blood were measured at the start and end of the feeding trial. There was no difference in feed intake, body weight gain, digestibilities of nutrients among all groups. The serum cholesterol level was found to be significantly lower (p<0.05) in culled carrot fed groups (II and III) whereas glutathione peroxidase and catalase activity showed a significant increase (p<0.05) in treatment groups than the control (CON) group. However, serum levels of ALT, AST and ALP were found comparable among all three groups. In conclusion, the feeding of culled carrots at 10 and 20% levels in the concentrate feed to the rabbits resulted in reduced serum cholesterol level and improved antioxidant status without adverse effect on growth and nutrient utilization.